Evaluation of column-wise manipulations on Ultra-Performance Liquid Chromatography (UPLC) data for forensic soil discrimination - Lee, Loong Chuen (Tanjong Malim, 2022)
Evaluation of column-wise manipulations on Ultra-Performance Liquid Chromatography (UPLC) data for forensic soil discrimination by Lee, Loong Chuen